The Devonian Nekton Revolution - Kießling, Wolfgang; et al. (Lethaia, 2010)
Traditional analyses of Early Phanerozoic marine diversity at the genus level show an explosive radiation of marine life until the Late Ordovician, followed by a phase of erratic decline continuing until the end of the Palaeozoic, whereas a more recent analysis extends the duration of this early radiation into the Devonian. This catch-all approach hides an evolutionary and ecological key event long after the Ordovician radiation: the rapid occupation of the free water column by animals during the Devonian. Here, we explore the timing of the occupation of the water column in the Palaeozoic and test the hypothesis that ecological escalation led to fundamental evolutionary changes in the mid-Palaeozoic marine water column. According to our analyses, demersal and nektonic modes of life were probably initially driven by competition in the diversity-saturated benthic habitats together with the availability of abundant planktonic food. Escalatory feedback then promoted the rapid rise of nekton in the Devonian as suggested by the sequence and tempo of water-column occupation. Devonian, diversity, ecology, food webs, nekton, plankton, radiation. © 2009 The Authors, Journal compilation © 2009 The Lethaia Foundation.
UnivIS-Import:2015-03-09:Pub.2010.nat.dgeo.IGM.LP.thedev